In Vitro Influence of Prophylaxis Cleaning on Enamel Remineralization with Casein Phosphopeptide-Amorphous Calcium Phosphate - Mona Zeitouny; Hasan Fayyad-Kazan; Herve Tassery; Hussein Fayyad-Kazan (eJournal of Oral Maxillofacial Research)
Objectives: This randomized controlled in vitro 4-arm trial study aimed to study the remineralization potential of Recaldent™ and assess the effects of prophylaxis cleaning and MI Varnish® on enhancing this remineralization potential.